The Relationship between the Strategy of Coping with Difficult Social Situations… by Students with Mild Intelectual Disability and their Overt Aggressive Behaviour - Mikrut, Adam (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The present study is an attempt to verify the assumption of mutual relationship between coping strategies in difficult social situations by students with mild intellectual disability and their aggressive behaviour displayed in other everyday situations and circumstances. Justification of this assumption can be found in the repetitive and ensuing sequence of occurrences and processes: the deficits in perceptual-cognitive, intellectual and emotional-motivational functions which are characteristic of this group of people, make it difficult for them to understand and evaluate the interpersonal relationships, hence they perceive them as threatening. Emotional tension arising from those situations is released by using destructive strategies including aggression. The repetition of this experience leads to destructive behaviours which are manifested in various everyday situations and circumstances. These fixed behaviour patterns are then used in subsequent difficult social situations etc.